2014
DOI: 10.2478/popore-2014-0028
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of heavy metals resistant heterotrophic bacteria from soils in the Windmill Islands region, Wilkes Land, East Antarctica

Abstract: Abstract:In this study, selected heavy metals resistant heterotrophic bacteria isolated from soil samples at the Windmill Islands region, Wilkes Land (East Antarctica), were character− ized. Phylogenetic analysis revealed affiliation of isolates to genera Bacillus, Lysini− bacillus, Micrococcus and Stenotrophomonas. The strains were found to be psychrotolerant and halotolerant, able to tolerate up to 10% NaCl in the growth medium. The Minimum In− hibitory Concentration of the seven heavy metals Cr, Cu, Ni, Co,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Moreover, in 162 strains co-resistance (i.e., joint resistance to at least two toxic ions) phenotypes were revealed, which indicates that this phenomenon is not restricted to bacteria originating from the heavily contaminated regions. This high number of heavy metal-resistant bacteria in the Antarctic region may be surprising; however, it is in agreement with the results of other studies (De Souza et al 2006Tomova et al 2014Tomova et al , 2015. Moreover, the high incidence of resistance to heavy metals suggests that bacteria are able to cope and/or adapt to the occurrence of "pollutants" even in low humanimpacted environments (Lo Giudice et al 2013).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, in 162 strains co-resistance (i.e., joint resistance to at least two toxic ions) phenotypes were revealed, which indicates that this phenomenon is not restricted to bacteria originating from the heavily contaminated regions. This high number of heavy metal-resistant bacteria in the Antarctic region may be surprising; however, it is in agreement with the results of other studies (De Souza et al 2006Tomova et al 2014Tomova et al , 2015. Moreover, the high incidence of resistance to heavy metals suggests that bacteria are able to cope and/or adapt to the occurrence of "pollutants" even in low humanimpacted environments (Lo Giudice et al 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Studies of extreme, polar environments characterized by a still limited anthropogenic influence (e.g., High Arctic or Antarctica) are of great importance, as they may reveal novel genes encoding heavy metal-resistance and metabolism mechanisms, and show the role of naturally occurring microorganisms in biogeochemical cycles. The results of several studies revealed that bacteria isolated from various Arctic and Antarctic environments show resistances to various toxic, antimicrobial agents, such as antibiotics and heavy metals (De Souza et al 2006Lo Giudice et al 2013;Mangano et al 2014;Moller et al 2014;Tomova et al 2014;Perron et al 2015;Rahman et al 2015;Tomova et al 2015;González-Aravena et al 2016;Rodriguez-Rojas et al 2016). However, overall knowledge on the resistome of polar bacteria is still rather limited, and the lack of a systematic approach, combining chemical, microbiological, and molecular analyses, is apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance of psychrotrophic Antarctic bacteria isolated from terrestrial and aquatic samples has been reported by several research groups (De Souza et al 2006, Wong et al 2011, Tomova et al 2014a. Strain INACH3013 was resistant to nine antibiotics, of which four were β-lactam antibiotics and the other five belonged to different antibiotic groups (metronidazole, mupirocin, nitrofurantoin, sulphonamide compounds and trimethoprim).…”
Section: Discussionmentioning
confidence: 93%
“…2011, Tomova et al . 2014a). Strain INACH3013 was resistant to nine antibiotics, of which four were β-lactam antibiotics and the other five belonged to different antibiotic groups (metronidazole, mupirocin, nitrofurantoin, sulphonamide compounds and trimethoprim).…”
Section: Discussionmentioning
confidence: 99%
“…Siachen glacier is known as the world’s highest non-polar glacier and considered as the highest and world’s biggest garbage dump, 40% of which are plastics and metals, worn out gun barrels, splinters from gun shelling, empty fuel barrels and burnt shelters, which permanently pollute glacial ice and water and leach toxins like cobalt, cadmium, chromium and other metals due to unavailability of natural biodegrading agents [ 60 ]. The heavy metal tolerance could possibly be due to these pollutants, and could possibly lead to antibiotic resistance too, as metal and antibiotic resistance is often present as co-resistance [ 61 ].…”
Section: Discussionmentioning
confidence: 99%